Investigation of HUAWEI Phone Product Opinions Using Aspect Based Sentiment Analysis (ABSA) on Customer Reviews - Fu, Ruidan (2022)
With the rapid development of e-commerce, posting reviews online has become an important way for people to express their views and transfer their experience. The reviews not only assist individuals in making choices, but also assist businesses of finding valuable information to help improve the sales. In order to processing the unstructured text, sentiment analysis is useful of mining opinions and sentiments. In this research, customer reviews of HUAWEI phone products on Amazon were collected to bring insights for the company. By combining the topic modeling and the dependency analysis of the reviews, the study gets a more comprehensive and more interpretable results to inform the business.